Господарчi споруди Вовчанського городища: проблеми реконструкцiї та iнтерпретацiї - Колода, В.В. (Археологія, 2020)
Розглядаються залишки господарчих будівель, що виявлені на Вовчанському городищі у Харківській обл., яке належить до північно-західних територій Хозарського каганату (лісостеповий регіон салтівської культури середини VIII — середини Х ст. н. е.). На підставі археологічних та етнографічних даних, а також можливостей ґрунтів і природного оточення щодо будівельного матеріалу, пропонуються реконструкції окремих господарчих будівель. Виходячи з етнополітичної ситуації визначається можливе призначення цих споруд. Волчанское городище расположено на восточной окраине г. Волчанск в Харьковской обл. Оно принадлежит салтовской культуре (середина VIII — середина Х в. н. э.), которая отражает материальные и культурные остатки Хазарского каганата. Памятник является центром одного из полутора десятков микрорегионов Хазарского каганата, открытых в среднем течении Северского Донца. Городище занимает высокий мыс правого берега р. Волчья (правый приток Северского Донца). Оно имеет одно дворище с тройной системой обороны, которая состояла из валов, рвов и эскарпов. Хозяйственные сооружения были найдены в северной части цитадели, а также между внешней и средней линиями защиты. В пределах пристеночного пространства цитадели открыта небольшая хозяйственная зона с незначительными по площади хозяйственными помещениями из глинобитных стен. Они, скорее всего, служили для хранения продовольственных запасов, которые были предназначены для небольшого количества потребителей (например, для гарнизона цитадели?). В южной части городища исследовано девять хозяйственных сооружений, что располагались на расстоянии 4,0—6,0 м друг от друга (при отсутствии жилищ по соседству). Все они различны в плане и по конструкции. Была предложена реконструкция наиболее целостных из них. При этом были учтены результаты археологических исследований, строительное качество грунтов, строительный материал из природного окружения, наличие инструментов и их возможности в обработке сырья, а также этнографические данные по традиционному строительству местного населения в ХVIII—ХІХ вв. Данные сооружения предназначались для хранения пищевых запасов в деревянных или плетеных из лозы и лыка коробах и иных ёмкостях, а также в мешках (кожаных или тканевых) и в керамической таре. Предлагается несколько гипотез относительно их назначения: — Запасы могли принадлежать населению местной сельскохозяйственной округи для их использования в период внешней угрозы, что вполне возможно с учётом гражданской войны в Хазарии в начале ІХ в. — Запасы могли создаваться для употребления военным гарнизоном, который мог пребывать в цитадели городища для обеспечения военного давления на славян. — Рассмотренные помещения могли использоваться для временного хранения собранного у местного населения зернового урожая (а, возможно, и дани, собранной со славян) перед его отправкой в распоряжение центральной власти каганата. Сходство двух выявленных хозяйственных помещений в раскопе 3 свидетельствует, что работы исполнялись одной группой строителей и по одному плану. Конструктивное разнообразие хозяйственных помещений в раскопе 4 свидетельствует, что они создавались разными группами мастеров. Vovchansk hillfort is located in the eastern border area of Vovchansk city in Kharkiv Region. It belongs to the Saltiv archaeological culture (mid. VIII — mid. X centuries), which reflects material and cultural remains of the Khazar Khaganate. This site is among one and a half dozens of microregions in the Khazar Khaganate located in the middle stream of the Siverskyi Donets. The site is located on the cape of the right bank of the Vovcha River (right inflow of the Siversky Donets). It has one yard with a threefold defence system that includes earthen walls, ditches and scarps. Household buildings were discovered in the northern part of the citadel, and between outward and inward defensive lines. A small household zone was found within the range of the space near citadel walls; its household buildings were of a small area, with mud-brick walls. They were likely to serve for food supply storage meant to be delivered for a small number of consumers (for example, for the citadel garrison). Nine household buildings found between exterior and middle defence lines were investigated in the southern part of the hillfort; they are located in 4.0—6.0 meters from one another (in the absence of nearby dwellings). All of them are different in their plan and construction. The reconstruction of the most extant ones is offered in the article. The following things were taken into account: results of archaeological research, construction quality of grounds, surrounding nature of construction raw materials, presence of implements and their feasibility of raw materials processing, and also ethnographic data on traditional construction of the population in XVIII—XIX centuries. These buildings were designed for food preservation in wooden or vine- or fibre-braided baskets and other containers, also in bags (of leather or tissue) and ceramic tare. As to the purpose of these food stocks, some hypotheses are offered. The 1st hypothesis: the storage could belong to the local surrounding population in the times of external threat for the residents of the nearby settlements; it seems probable in the light of the civil war in Khazaria at the beginning of the 9th century. The 2nd hypothesis: food supply could be stored to be consumed by the garrison, which could be located in the hillfort citadel for creating military pressure on the Slavs. The 3rd hyposesis: the mentioned buildings could be used for temporary retention of the corn harvest (and probably, the Slavs’ tribute) reaped by the local community before its shipping at the disposal of the central authority of the Khaganate. Similarity between two discovered household buildings in the excavation site No. 3 points to the fact that the work was done by the same craftsmen group following the common plan. Constructive diversity of household buildings in the excavation site No. 4 shows that they were created by different craftsmen groups.